2011
DOI: 10.1021/pr2006878
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Identification of Calcium Oxalate Monohydrate Crystal-binding Proteins on Apical Membrane of Distal Renal Tubular Epithelial Cells

Abstract: Adhesion of calcium oxalate monohydrate (COM) crystals onto apical surface of renal tubular epithelial cells is a crucial mechanism for crystal retention, leading to kidney stone formation. Various proteins on apical membrane may bind to COM crystals; however, these crystal-binding proteins remained unidentified. The present study therefore aimed to identify COM crystal-binding proteins on apical membrane of distal renal tubular epithelial cells. Madin-Darby Canine Kidney (MDCK) cells were cultivated to be pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 31 publications
3
48
0
1
Order By: Relevance
“…COM crystal adhesion on the renal tubular cell surface is an important initiating step in kidney stone formation. Our previous study demonstrated a number of potential COM crystal receptors on renal tubular cell membranes, which can bind to COM crystals [44]. Interestingly, one of such potential COM crystal receptors is α-enolase, of which cellular level was increased upon testosterone treatment in our present study (Figs.…”
Section: Validation Of Testosterone-induced Increase In Cellular α-Ensupporting
confidence: 58%
“…COM crystal adhesion on the renal tubular cell surface is an important initiating step in kidney stone formation. Our previous study demonstrated a number of potential COM crystal receptors on renal tubular cell membranes, which can bind to COM crystals [44]. Interestingly, one of such potential COM crystal receptors is α-enolase, of which cellular level was increased upon testosterone treatment in our present study (Figs.…”
Section: Validation Of Testosterone-induced Increase In Cellular α-Ensupporting
confidence: 58%
“…Our previous expression proteomics study identified α-enolase as a COM crystal-binding protein on apical membranes of renal tubular epithelial cells by quadrupole time-of-flight (Q-TOF) tandem mass spectrometry (MS/MS)4. Additional supportive evidence has demonstrated that expression level of α-enolase was increased and decreased after renal tubular cells were treated with stone aggravators1213 and inhibitor14, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a number of potential COM crystal-binding molecules and/or proteins expressed on the apical membranes of renal tubular epithelial cells have been identified234. After renal tubular cell injury by numerous inducers, the injured renal tubular cells showed increased expression of COM crystal-binding molecules/proteins in concordance with the enhanced COM crystal binding on the cell surfaces5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…chemical-based precipitation and centrifugation-based methods) have been proven to be problematic and ineffective for isolation/purification of apical membrane proteins by contaminations of other cellular compartments, particularly basolateral membranes [9]. Using the apical membrane peeling method, a recent MS-based proteomics study successfully identified almost a hundred of potential CaOx crystal receptors on apical membrane of renal tubular cells that may be the targets for prevention of the stone formation/ recurrence [10]. In addition, another method known as membrane protein 'shaving' is particularly useful for the development of drug targets and defining potential protein receptors [11].…”
Section: Investigations Of Apical Membrane Proteins From Renal Tubulamentioning
confidence: 99%